Genomic diversity of resistant and virulent factors of Burkholderia pseudomallei clinical strains recovered from Guangdong using whole genome sequencing - Shafiq, Muhammad; Ke, Bixia; Li, Xin; Zeng, Mi; Yuan, Yumeng; He, Dongmei; Deng, Xiaoling; Jiao, Xiaoyang (Frontiers in Microbiology, 2022)
Background Burkholderia pseudomallei (B. pseudomallei) is a highly infectious agent and causes melioidosis, in both humans and animals, which is endemic in Southeast Asia and Northern Australia. Objectives This study aims to determine the molecular epidemiology, resistant determinants, and genomic diversity of the clinical isolates of B. pseudomallei to further elucidate the phylogenetic and evolutionary relationship of the strains with those in other endemic regions. Methods In this study, we obtained eight clinical B. pseudomallei isolates from Guangdong province from 2018 to 2019. All the isolates were sequenced using the Illumina NovaSeq platform. The draft genomes of B. pseudomallei were further used to find antibiotic-resistant genes (ARGs), virulence factors, and gene mutations. Multilocus sequence typing (MLST) and single nucleotide polymorphism (SNP) analysis were performed to characterize the diversity and epidemiology of the strains. Results All isolates were susceptible to antibiotics commonly used for melioidosis treatment. Class D beta-lactamases genes OXA-57 and OXA-59, as well as various mutation factors such as amrA, amrB, omp38, gyrA, and ceoB were identified. MLST analysis of the B. pseudomallei strains identified eight different sequence types (STs): ST1774, ST1775, ST271, ST562, ST46, ST830, ST1325, and ST10. Phylogenetic analysis found that the strains used in this study showed high genetic diversity. We also report 165 virulence factors among B. pseudomallei strains responsible for different neurological disorders, pneumonia, skin lesions, and abscesses. All strains recovered in this study were susceptible to commonly used antibiotics. However, high genetic diversity exists among the isolates. The surveillance, diagnosis, and clinical features of melioidosis varied in different geographical locations. These regional differences in the clinical manifestations have implications for the practical management of the disease. Conclusion The present study reports the identification of different mutation and virulence factors among B. pseudomallei strains responsible for different neurological disorders, pneumonia, skin lesions, and abscesses.